Formulation optimization of furosemide floating-bioadhesive matrix tablets using waste-derived Citrus aurantifolia peel pectin as a polymer - Ebrahim Abdela Siraj; Yohannes Mulualem; Fantahun Molla; Ashagrachew Tewabe Yayehrad; Anteneh Belete (Scientific Reports)
Abstract Natural polymers such as pectin have garnered significant interest in recent years due to their potential applications in gastroretentive drug delivery systems. Gastroretentive dosage forms are intended to extend the emptying time of drugs in the gastrointestinal tract. Accordingly, this study was aimed to examine the use of pectin as a floating and mucoadhesive polymer using furosemide as a model drug. The citrus peel pectin was extracted from local Citrus aurantifolia tree fruit peel using hot water extraction technique. FTIR and DSC analyses were performed to investigate the compatibility of the pectin extracted with furosemide. C. aurantifolia peel yielded 34.4% (w/w) purified pectin with a degree of esterification of 85.49%. FTIR and DSC analysis revealed that the citrus peel pectin powder is compatible with furosemide. Based on preliminary study, pectin and effervescent agent concentration were identified as significant independent variables. Hence, their influence on five response variables (floating duration, bioadhesive strength, swelling index, drug release at 1 h, and drug release rate) were further studied and optimized using central composite design (CCD). Accordingly, the CCD model predicted an optimum formulation at 22.3% of pectin concentration and 5% of effervescent agent. Under this condition, the Design-Expert software predicted floating duration (14.07 s), bioadhesive strength (28.57 g), swelling index (254.08%), drug release at 1 h (27.86%), and drug release rate (28.045%/h−1/2). The validity of the predicted optimum formulation was confirmed experimentally. The optimized tablet formulation showed pharmacopeial acceptable characteristics. In conclusion, the results of this study suggest that waste-derived citrus pectin can be considered as an abundant alternative pharmaceutical excipient in the formulation and manufacture of floating and bioadhesive matrix tablets with favorable floating and bioadhesion characteristics.